2014
DOI: 10.1111/ecc.12207
|View full text |Cite
|
Sign up to set email alerts
|

Preferences of colorectal cancer patients for treatment and decision-making: a systematic literature review

Abstract: Treatment decisions in life-threatening diseases, like colorectal cancer (CRC), are crucial, since they have a great impact on patient's survival and health-related quality of life. Thereby, the inclusion of patient's preferences becomes more and more important; however, these first need to be identified. Therefore, we conducted a systematic literature review in 12 electronic databases, published between 2000 and 2012, in order to identify patient's preferences concerning treatment preferences and involvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 34 publications
1
31
0
Order By: Relevance
“…With this in mind, the present results are similar to those reported in a recent review of decision-making preferences across a broad range of patient groups 17. However, a colorectal cancer-specific review reported that the majority of patients preferred a passive role in decision making, based on studies published between 2003 and 2008 15. Preferences of patients with GI cancer may have shifted over time.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…With this in mind, the present results are similar to those reported in a recent review of decision-making preferences across a broad range of patient groups 17. However, a colorectal cancer-specific review reported that the majority of patients preferred a passive role in decision making, based on studies published between 2003 and 2008 15. Preferences of patients with GI cancer may have shifted over time.…”
Section: Discussionsupporting
confidence: 87%
“…Previous research examining choice among patients with cancer has typically focused on treatments,15 rather than providers. Patients with cancer have largely been excluded from studies investigating provider choice.…”
Section: Introductionmentioning
confidence: 99%
“…These steps are undertaken in parallel to the publication for preferences of colorectal cancer patients by Damm et al . ().…”
Section: Methodsmentioning
confidence: 97%
“…2014Blanchard [13]2016Assessing head & neck cancer patient preferences & expectations: asystematic review“We conducted a systematic review of the current evidence regarding the preferences & priorities of patients with head & neck cancer.”Sept. 2016Blinman [14]2010Patients’ preferences for chemotherapy in non-small-cell lung cancer: a systematic review“To find, evaluate & summarise studies quantifying the survival benefits that cancer patients judged sufficient to make chemotherapy for NSCLC worthwhile.”2009Bradley [15]2007Review of patterns of practice & patients’ preferences in the treatment of bone metastases with palliative radiotherapy“To review the patterns of practice among radiation oncologists & patients’ preferences in the treatment of bone metastases with palliative radiotherapy.”June 2006Brooker [16]2013Quantitative patient preference evidence for health technology assessment: a case study“To explore the feasibility & desirability of incorporatingpatient preferences within the health technology assessment process by working through a case study.” [COPD]March 2011Currie [17]2014A systematic review of patient preference elicitation methods in the treatment of colorectal cancer“To assess the use of patient preference in colorectal cancer treatment.”March 2014Damm [18]2014Preferences of colorectal cancer patients for treatment & decision-making: a systematic literature review“To identify the preferences of CRC patients with regard to treatment preferences & involvement in the decision-making process regarding treatment choices.”Sept. 2012Eek [19]2016Patient-reported preferences for oral vs. intravenous administration for thetreatment of cancer: a review of the literature“To evaluate the administration preferences of cancer patients, specifically between oral & intravenous treatment, as well as the factors contributing to preference.”Jan.…”
Section: Resultsmentioning
confidence: 99%